2020
DOI: 10.2147/nsa.s232517
|View full text |Cite
|
Sign up to set email alerts
|

<p>Loading Amlodipine on Diamond Nanoparticles: A Novel Drug Delivery System</p>

Abstract: Background: Diamond nanoparticles (Nanodiamond) are biocompatible drug delivery platforms with outstanding surface properties. Their passage into the brain has been confirmed previously. Thus, nanodiamond could provide a drug delivery system to shuttle several drugs through the blood-brain barrier (BBB) which represents a real challenge for the effective delivery of several drugs into the brain. Amlodipine is a calcium channel blocker that cannot pass through BBB and may elicit neuroprotective effects to rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We began exploring other inhibitors, such as channel blockers, to see if other routes of uptake are possible due to the characteristics CNDs have [ 69 ]. After exploring our selected known channel blocking inhibitors, the results displayed that amlodipine, a calcium channel blocker [ 40 ], increased the fluorescence of CNDs. Previous studies completed on human umbilical vein endothelial cells (HUVEC) suggested that when a build-up of calcium occurs internally within endothelial cells, this stimulates an increase in endocytosis events [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…We began exploring other inhibitors, such as channel blockers, to see if other routes of uptake are possible due to the characteristics CNDs have [ 69 ]. After exploring our selected known channel blocking inhibitors, the results displayed that amlodipine, a calcium channel blocker [ 40 ], increased the fluorescence of CNDs. Previous studies completed on human umbilical vein endothelial cells (HUVEC) suggested that when a build-up of calcium occurs internally within endothelial cells, this stimulates an increase in endocytosis events [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapy with nanoparticles has been inserted into treatment modalities, from cardiovascular treatments to oncology treatments. Due to the small size of nanoparticles, they can be suitable for crossing the blood-brain barrier (BBB), specifically nanodiamonds with conjugating potential [ 33 ]. Researchers are trying to formulate a conjugation between a drug that does not cross the BBB, such as amlodipine, and nanodiamonds that do cross it [ 34 ].…”
Section: Impact Of Nanotechnology In Pancreatic Cancermentioning
confidence: 99%
“…Below are some of them that have already been successfully loaded in NPs as anti-hypertensive therapy. Amlodipine into nanodiamond particles is ready to be tested in vitro, 71 liposomes enhanced lacidipine bioavailability, 72 lomerizine in nanoparticle-based carriers suppressed Ca 2+ influx in PC12 cells in response to glutamate. 73 In vitro testinnig revealed that PLGA NPs showed longer duration of felodipine release with reduced burst release compared with pure drug paralleled by a complete biocompatibility in in vivo toxicity study in albino mice.…”
Section: Reducing Intracellular Calciummentioning
confidence: 99%